Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set - Page 476: 16



Work Step by Step

RECALL: $(g/f)(x)=\dfrac{g(x)}{f(x)}$ Thus, $(g/f)(x) = \dfrac{x^2-5}{-2x+3}$ To evaluate the given expression, substitute $-3$ to $x$ in the equation above to obtain: $g(-3)/f(-3) \\= (g/f)(-3) \\=\dfrac{(-3)^2-5}{-2(-3)+3} \\=\dfrac{9-5}{6+3} \\=\dfrac{4}{9}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.